Altitude-dependent Variations in Some Morphological and Anatomical Features of Anatolian Chestnut - Gizem Özdikmenli; Nurcan Yiğit; Halil Barış Özel; Hakan Şevik (BioResources, 2024)
Morphological measurements of Anatolian chestnut (Castanea sativa Mill.) leaves were done within the borders of Abana district of Kastamonu province. The study was conducted using mixed (oak, beech, hornbeam, black pine, and yellow pine) medium (41% to 70%) and fully closed (71% to 100%) stands. Some leaf parameters, such as leaf blade width, petiole length, leaf blade length, leaf length, distance between lateral veins, teeth width, teeth length, the angle between the leaf base and the petiole, and the angle between the midrib and lateral veins, were measured. Moreover, stomata of the leaves picked up from precise altitudes were observed under a scanning electron microscope. The differences between fibre elevation, fibre wall thickness, elasticity coefficient, rigidity coefficient, Muhlstep rate, and Runkel ratio were found in the wood samples taken from different altitude zones. It was found that altitude did not affect leaf blade width, fibre length, fibre width, felting ratio, and lumen width. However, it was determined that altitude affected other studied characteristics.